O ENVELHECIMENTO, A DOENÇA DE ALZHEIMER E AS CONTRIBUIÇÕES DO PROGRAMA DE ENRIQUECIMENTO INSTRUMENTAL (PEI) - Antonia Rozeli Roberto de Oliveira (CAEN, 2010)
This article suggests that the aging process has unique and distinct features. A distinction is made between normal and pathological aging. Actually we are concerned that a successful aging is in close relationship with the pre-vention of diseases, and maintenance of physical and cognitive activities. Epidemiological studies show that elderly people with mild cognitive deficts are at greater risk of developing Alzheimer's disease. This disease affects brain function, primarily memory, and also speech, executive functions, praxias and gnosias. Besides the current pharmacological approach, alterna-tive therapies, like neuropsychological rehabilitation, are in current use and contributes in a great amount to the improvement of cognitive and behav-ioral functions. In this article we gave special attention using PEI and EAM, in neuropsychological rehabilitation programs directed to Alzheimer`s dis-ease, focusing the improvement of residual functions and aiming the reduc-tion of the impact that this disease brings to the quality of life.